Medulloblastoma - Shah, Azaz Ali (Journal of Postgraduate Medical Institute, 2011)
In our series the medulloblastoma accounted for nearly 16% cases of tumors population as opposed to 25% in the prescribed text. These occurred in early two decades of life; with a survival rate much less in five years, but practically nearly the same after one year as predicted.